Effect of O/W process parameters on Crataegus azarolus L nanocapsule properties - Esmaeili, Akbar (BioMed Central, 2013)
BACKGROUND: Nanocapsules have many applications in the drug, cosmetic, fragrance, and food industries. In this study, Crataegus azarolus L. nanocapsules were prepared by a modified emulsion diffusion technique. METHODS: In this technique a shell was first made from the polyester triblock copolymer poly(ethylene glycol)-poly(butylene adipate)-poly(ethylene glycol) (PEG-PBA-PEG) and then olive oil was set as the core of the nanocapsule by a method known as the polymer deposition solvent evaporation method. Varying amounts of C. azarolus extract, polymer, and olive oil were mixed in acetone and then added to water on a shaker. Finally, the acetone was removed by vacuuming. RESULTS: The size of the prepared nanocapsules were measured with a particle size analysis report (PSAR) and identified by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and nuclear magnetic resonance (NMR). CONCLUSIONS: Our experiments showed that the size of the nanocapsules depends on the preparation conditions, i.e., the ratio of polymer to oil and concentrations of polymer and plant extract. A ratio of 1:0.25 polymer to oil was shown to be more suitable for the formation of smaller nanocapsules of C. azarolus.